Starania wrocławskiego Kościoła o uzyskanie swobody gospodarczej i sądowej na swych dobrach w I poł. XIII wieku – umowa z 1249 r. - Norbert Jerzak (Wrocławski Przegląd Teologiczny)
By the end of the twelfth century the bishopric of Wrocław owned a lot of goods and become a major economic power, although it was not sovereign against princely power. On the lands, which were granted to the Bishop, were goods belonging to the prince or knights and it was the separation of power. This situation has helped the prince to keep the right to use the benefice of ecclesiastical property. The Church had to apply for the immunity privileges, defining the power of the Church to his estate (the statute of Łęczyca from 1180), the acquisition of the economic and judicial immunity and the right to the free judiciary with the state as a judgment executor. In the bishopric of Wrocław the process to obtain the immunity was slower, as a result of disputes between bishops and silesian princes. Most of these disputes ended in a settlement, more or less favorable to the Church. The dispute between Prince Henry the Bearded and Bishop Thomas I was more hardened. The Bishop accused the prince in a letter to Rome of violating the immunity of Churches goods and forcing the population of the episcopal estates to work for the prince. Prince Henry doesn’t appear to call of the papal legate to resolve controversial issues, he was covered by excommunication, forcing the prince to intervene in Rome. The dispute lasted until March 18, 1238, to the death of Prince Henry the Bearded. After his death, his son Henry the Pious took the power, who was implacable in fundamental issues. In 1239, after the intervention of Pope Gregory IX, there is a trade-off between Prince Henry II and the Bishop of Wrocław. The first half of the thirteenth century, despite the political turmoil in Silesia, inefficient power of the son of Henry – Boleslaw Rogatka and the division of Silesia, has brought many law benefits to Church of Wrocław, which were written in the contract from June 26, 1249 in St. Giles Church in Wrocław. This contract has been written in form of rights articles of the Church and theprince in the castellany Milicz and regulates the legal relations between the two authorities. It is lack of informations about class of population and the existing german colonization in the county of Milicz. Issues raised in the agreement can be divided according to the general system of the Middle Ages into two categories: causae maiores, belonging generally to the prince and causae minores, belonging to the patrimonial judiciary (thefts, beatings, disputes and others). The range of ducal and ecclesiastical rights in Milicz contained in the contract was based on two elements of administrative system: burgum – urban settlement, including the castle, the other prison management indicating the administrative and judicial nature. Location of this burgum by the Church took place before the signing of the contract (1241–1249) and there judicial matters of maleficium controveria vel iniuria and futurum belonged to the Church castellan. The exception was the trial of the people caught in the crime in burgum or on his salary. Depending on the location, time and the causer of the crime, the penalty and the income from court fines were differentiated. The same principle was binding for the murder, so-called head. Another discussed issue was the prison of Milicz (carcer). This prison was located in the interior of the castle or in the dark of the castle or in a tower. In § 10 of the contract was stated that „the prison has always belonged and still belongs to the Church” (however it really happend to the end of the eleventh century). In the Church prison there were not only doing their time the people because of the Church judgment but also prisoners of the prince, the prince probably hadn’t have his own prison. In the contract was raised the issue about security against escapes of prisoners. It was determined, that the amount of the fine and the guilt will depend on the number of fugitives and on whose judgment they have been convicted. The contract of 1249 refers in general terms about social composition of prisoners. From this documents can only be deduced, that the penalty for the same crime were different depending on social and financial status. Based on this contract, it can be analyzed the process of taking over the secular reins of the Church in castellany Milicz, which will be completed in 1290. In the agreement was settled the case of the judiciary power of the Church castellan, who had the right to sue, prosecute, punish and dismiss the subjects of the Church on the territory of castellan and the whole income from this activity belonged to him. Over time developed the range of his power. Similar agreements the Church signed in 1241 in the duchy of Opole, in 1253 in Głogow, in 1260 in Legnica. After analyzing these agreements, it should be noted, that the authority of the Church in the castellany Milicz was much bigger than in other areas of Silesia and in the middle of the thirteenth century the authority of the Church exceeded the power range of princely castellan. In 1290 follows the taking over reins by the Church on the territory of the castellan, but it was not a full judicial and economic immunity.